Vancomycin-intermediate Staphylococcus aureus isolates are attenuated for virulence when compared with susceptible progenitors. (October 2017) - Cameron, D.R.; Lin, Y.-H.; Trouillet-Assant, S.; Tafani, V.; Kostoulias, X.; Mouhtouris, E.; Skinner, N.; Visvanathan, K.; Baines, S.L.; Howden, B.; Monk, I.R.; Laurent, F.; et al.
Abstract: Objectives: Vancomycin-intermediate Staphylococcus aureus (VISA) is associated with genetic changes that may also impact upon pathogenicity. In the current study, we compared the virulence of clinical VISA strains with their isogenic vancomycin-susceptible progenitors (VSSA). Methods: Production of the critical virulence protein, α toxin, was assessed using Western blot analysis and was correlated to agr activity using a bioluminescent agr -reporter. Cytotoxicity and intracellular persistence were compared ex vivo for VSSA and VISA within non-professional phagocytes (NPP). Virulence and host immune responses were further explored in vivo using a murine model of bacteraemia. Results: VISA isolates produced up to 20-fold less α toxin compared with VSSA, and this was corroborated by either loss of agr activity due to agr mutation, or altered agr activity in the absence of mutation. VISA were less cytotoxic towards NPP and were associated with enhanced intracellular persistence, suggesting that NPP may act as a reservoir for VISA. Infection with VSSA strains produced higher mortality in a murine bacteraemia model (≥90% 7-day mortality) compared with infection with VISA isolates (20% to 50%, p <0.001). Mice infected with VISA produced a dampened immune response (4.6-fold reduction in interleukin-6, p <0.001) and persistent organ bacterial growth was observed for VISA strains out to 7 days. Conclusions: These findings highlight the remarkable adaptability of S. aureus, whereby, in addition to having reduced antibiotic susceptibility, VISA alter the expression of pathogenic factors to circumvent the host immune response to favour persistent infection over acute virulence.